Extraction And Characterization Of Policosanol From Wheat Germ - Srisaipet, Anakhaorn; Keawprom, Pitchaporn (International Journal of Engineering and Technology, 2018)
Policosanol is a mixture of long chain alcohols, with chain lengths varying between 20 to 36 carbon atoms that has been proven to be effective in lowering cholesterol levels in the body. The objective of this research is extraction the policosanol from wheat germ and characterization of the alcohol. The dried milled wheat germ was hydrolyzed by refluxing with 1.0 N methanolic NaOH at 80 °c for 45 minutes. The product hydrolyzed are consists of long chain alcohol (policosanol) and free fatty acid. The purification of hydrolyzed products was performed by extraction with dichloromethane twice follow by pH adjustment to 7 using 6 N hydrochloric acid thereby the purity of policosanol was confirmed by TLC. The aliphatic long chain alcohols composition in policosanol were establish in 18-34 carbon atoms analyzed by gas chromatographic technique (GC). Wheat germ can be a viable policosanol source for health benefits product development or food supplements.
Keywords: Beeswax; Hydrolysis; Microwave; Policosanol